In vivo and in vitro genotoxicity studies of aqueous extract of Xanthium spinosum (Brazilian Journal of Pharmaceutical Sciences, 2012)
The use of plants as a source of palliative or cure for pathological conditions is quite common worldwide. Xanthium spinosum (Asteraceae), popularly known in Brazil as 'espinho de carneiro', is an annual weed from South America, which has been used by empiric medicine to treat neoplasias. Owing to the extensive use of the above-mentioned plant and to the lack of reports about the real effects of its infusion, current study evaluated the genotoxic potential of its aqueous extract at concentrations 0.02 g L-1, 0.1 g L-1 and 0.2 g L-1 by fish micronucleus test and by comet human leukocytes assay. The micronucleus test featured at least 50 cells with micronuclei to every 2,000 cells scored, as a mutagenic parameter. The comet assay was used as a parameter for assessing the level of cell damage and the damage index. Since no significant changes in strain cells exposed to the aqueous extract in the comet and micronucleus assays were reported, it seems that no genotoxicity evidence is extant at the concentrations and in the assays performed.